2019
DOI: 10.1002/admt.201900300
|View full text |Cite
|
Sign up to set email alerts
|

Supraparticles with a Magnetic Fingerprint Readable by Magnetic Particle Spectroscopy: An Alternative beyond Optical Tracers

Abstract: Marking and identification of materials is becoming increasingly important due to complex global resource and supply chains. Luminescent particle‐based markers have come to the forefront due to their small dimensions and their ability to be integrated in diverse materials. However, light‐absorbing materials can hardly be marked by these particles, thus leading to insufficient recycling rates of, e.g., black plastics. In this work, microparticles with a unique magnetic fingerprint are tailored by modification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…[21,22] In 2019, an approach to achieve six distinguishable magnetic fingerprints, by utilizing one magnetic nanoparticle type, was reported by our group. [23] Very recently, 29 different magnetic compositions were decoded by an automated decoding algorithm. [24] We understand the fingerprint of magnetic materials as their intrinsic signature, while the deliberate adjustment thereof should be denoted as magnetic codes.…”
Section: Introduction -A Miniaturized Magnetic Marker Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…[21,22] In 2019, an approach to achieve six distinguishable magnetic fingerprints, by utilizing one magnetic nanoparticle type, was reported by our group. [23] Very recently, 29 different magnetic compositions were decoded by an automated decoding algorithm. [24] We understand the fingerprint of magnetic materials as their intrinsic signature, while the deliberate adjustment thereof should be denoted as magnetic codes.…”
Section: Introduction -A Miniaturized Magnetic Marker Technologymentioning
confidence: 99%
“…[23,25] As magnetic signals can be transmitted through many materials that would not allow optical information to pass, such particles could be integrated within and not only on top of the surface of arbitrary objects, thus protecting the information against environmental harm but also against obvious detection and thus counterfeiting. [23,26] If such a magnetic particle marker could be achieved, it would equip materials with intelligence in many fields: it could further reduce the number of counterfeit products, which yield global annual damages of almost 500 billion US$ (2.5 % of global imports), [27] enable the identification and recycling of dark plastics, [23,[28][29][30] or permit the tracking-as well as monitoring-of goods and value chains, and finally could render quality control of materials and processes possible (Figure 1). [19] Although such a magnetic marker technology seems very promising, until now it is commonly accepted that too few magnetic codes are resolvable from magnetic markers, preventing research to achieve it.…”
Section: Introduction -A Miniaturized Magnetic Marker Technologymentioning
confidence: 99%
“…[ 215 ] In terms of SPs for recycling, only one publication from our group was found to date where SPs were described to contribute to recycling, indicating high capabilities for future contributions in this field. [ 216 ] Therein, a magnetic SP is suggested to enable sorting and identification of dark plastics. By variation of the composition, different magnetic fingerprints are resolved via magnetic particle spectroscopy ( Figure a).…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%
“…(a) Reproduced with permission. [ 216 ] Copyright 2019, Wiley‐VCH GmbH & Co. KGaA. (b, [ 220 ] c) [ 221 ] Reproduced with permission.…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%
“…Recent work indicated that magnetic particle spectroscopy (MPS) can sensitively detect changes induced by agglomeration of individual magnetic nanoparticles. [6][7][8] Due to the method's fast measurement speed and easily congurable measurement setup, it is potentially promising to in situ gain a better understanding of dynamically agglomerating magnetic particles in dispersion. 9 With respect to future applications, being able to precisely tailor agglomeration and thus magnetic properties of nanoparticles could be utilized to improve the efficiency of hyperthermia.…”
Section: Introductionmentioning
confidence: 99%